Special issue on plenary and invited papers from ICOPS 2009 - Farhat N. Beg; Michael G. Kong; Monica Blank (2010)
The nine papers in this special issue were originally presented at the 36th IEEE International Conference on Plasma Science (ICOPS) 2009, held jointly with the 23rd Symposium on Fusion Engineering (SOFE) in San Diego, CA, from May 31 to June 5, 2009.